Simulation-based analysis of lean practices implementation on the supply chain of a public hospital - Gabriela Aline Borges; Guilherme Luz Tortorella; Felipe Martínez; Matthias Thurer (Production)
Abstract Paper aims This article aims to evaluate the impact of Lean Production (LP) practices implementation on the supply chain of a public hospital. Originality Most implementations fall short of their goals because they are done in a fragmented way and not from a system-wide perspective. Our approach allows to anticipate errors of misguided LP implementations in healthcare organizations. Research method The implementation of a set of LP practices in the hospital`s supply chain was assessed by computational simulation modelling, focusing on one of the most financially important product families. Main findings Since the simulation model considers the variability of suppliers and customers as inputs, it allows the verification of the proposed inventory policies effectiveness, in order to avoid affecting the service level. Implications for theory and practice The proposition of a method that integrates value stream mapping into computational simulation modelling brings a differentiated approach to analyze lean implementation in a healthcare supply chain. The simulation model supports a more assertive decision-making process on lean implementation, allowing the organization to ensure that the quality and efficiency of healthcare is not affected.